Safety of a feed additive consisting of sepiolite for all animal species (Sepiol S.A. and Tolsa S.A.) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety of sepiolite as a technological feed additive for all animal species. In 2022, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) delivered an Opinion on the safety and efficacy of the same additive. The Panel concluded that sepiolite used as a feed additive is safe for the consumers and the environment, and efficacious as a thickener‐suspending agent, binder and anticaking agent in feed for all animal species under the proposed conditions of use. The additive was not considered an eye or skin irritant. However, it was considered a respiratory irritant, a respiratory and dermal sensitiser; owing to the dusting potential and its silica content, the additive was considered a risk by inhalation. Regarding the target species, in the previous Opinion, the Panel concluded on the safety of the additive for dairy ruminants. However, no conclusion could be drawn for all other species/categories. Based on the tolerance studies in chickens for fattening, weaned piglets and trout evaluated in the current assessment, and the one in dairy cows previously assessed, the Panel concluded that the inclusion of sepiolite at the maximum recommended level of 20,000 mg/kg complete feed is safe for all animal species.